External evaluation of UNCTAD peer reviews on competition policy - Melikyan, Lilit V. (United Nations New YorkUS, 2015)
Covers a period of four years during which fourteen countires were involved in the project. Aims to assesses systematically, objectively and credibly the project framework and design, project management and project performance. Is restricted to cover short and medium term outcomes only. Aims at drawing conclusions, making recommendations and identifying lessons learned from the implementation of the project.